MODIFIKASI PERILAKU MENURUNKAN KONSUMSI DAGING MERAH - Zulfa Diah Riptiana; Waluyo Budi Atmoko; Nang Among Budiadi (Jurnal Bisnis dan Kewirausahaan, 2025)
ABSTRACT This study aims to examine the influence of behavioral variables on reducing red meat consumption. The behavior of reducing red meat consumption is caused by the intention to reduce red meat consumption. The intention to reduce red meat consumption is influenced by attitudes towards red meat consumption, past experiences, awareness of the consequences of consuming red meat, and pro-environmental beliefs. Data were obtained through questionnaires that have been distributed to the community. The sampling technique used was Purposive Sampling with 200 respondents. Hypothesis testing used structural equation modeling analysis (Structural Equation Modeling - SEM) and logistic regression analysis. The results of the study obtained the results of the behavior of reducing meat consumption did not affect the intention to reduce red meat consumption, the intention to reduce red meat consumption did not affect attitudes towards red meat consumption, the intention to consume red meat did not have a positive effect on past experiences, and awareness of the consequences of consuming red meat had a positive effect on pro-environmental beliefs.